Neuroethical and Social Implications of Using Transcranial Electrical Stimulation to Augment Creative Cognition. Issue 3 (3rd July 2018) - Weinberger, Adam B.; Cortes, Robert A.; Green, Adam E.; Giordano, James
Abstract : Recent research indicates that transcranial electrical stimulation (tES) of specific brain regions can successfully improve various forms of creative cognition. Although the endeavor to increase human creative capacity is intriguing from a neuroscientific perspective, and of interest to the general public, it raises numerous neuroethico-legal and social issues (NELSI). This review explores these issues by considering (a) whether using brain stimulation to improve creative cognition qualifies as a 'treatment' or an 'enhancement, ' (b) how direct-to-consumer (DTC) and do-it-yourself (DIY) use of tES should be regarded and regulated, and (c) what the developing landscape of creativity-related neurostimulation could (and should) become.